The Use of Indirect Corrective Feedback to Eliminate Grammatical Errors in Students' Writing - Yusna Hannum; Absharini Kardena (Acitya: Journal of Teaching and Education, 2021)
This study aimed to find out the effect of using indirect corrective feedback to eliminate grammatical errors in students' writing. This research was conducted at SMKN 1 Padang Panjang because most of students still encounter problems in mastering writing text especially grammatical aspect. Most of the students' writing was founded many of grammatical error. Then, the students still did not get the appropriate feedback of the teacher toward their errors. And, the teacher also did not give the spesific feedback or treatment to help the students in reducing the error. This research used pre-experiment research. The researcher used one-group pretest posttest design. To determine sample, the researcher used purposive sampling technique. The data got from the pre-test and post-test in experiment class. To analyze the data, the resercher used the normality test and homogeneity test by using SPSS Statistics20 and to test the hypothesis the researcher used t-test formula and consulted the result into t-table with level of significant a=0.05. From the result and accounting the post-test of experiment class,it was founded that using indirect corrective feedback in eliminate grammatical error had better result than without indirect coreective feedback. It can be seen by comparing the t-obtained (2) that higher than the t-table (1.706).